Abortion: time to clarify Australia's confusing laws. - De Crespigny, L; Savulescu, J (2004)
Australian criminal law is a matter for states and territories. In relation to abortion, many laws are unclear and outdated, and are inconsistent between states and territories. Doctors practise under time constraints and on a case-by-case basis. Most current laws have grey areas that leave doctors vulnerable to accusations, negative publicity and career damage, especially in the case of late abortions. All jurisdictions should follow the Australian Capital Territory's lead in allowing women to access abortion without fear of criminal prosecution. Federal, state and territory governments should introduce a single clear national law on abortion, both in early and late pregnancy.